Contribution of Islamic Financial Institutions in Channeling Productive Financing to The Halal Industrial Ecosystem in Supporting Sustainable Development Goals (SDGs) - Peristiwo, Hadi; Yama, Arifeen (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2023)
Islamic finance is becoming part of that and can realize destination development sustainability in Indonesia, increasing its role as an institution. There is a lot of finance related to distribution financing productive to sector halal industrial ecosystem. Financing productive institutions Islamic finance against sector halal industry is the embodiment of economy sharia by kaffah (complete). This study uses a qualitative approach. The method used in this research is qualitative descriptive analysis. This study's data sources came from books, journals, and interviews with related informants about the role of Islamic finance in the distribution of productive financing to sector halal industrial ecosystems in supporting sustainable development goals (SDGs). Results show that instruments, both productive and investment financing provided and carried out by Islamic financial institutions, have an important role, especially in increasing the halal industrial sector. In addition, it can be seen that from the financing aspect, Islamic financial institutions channel more to the consumptive sector. The halal industry is an industrial sector with great potential if Islamic financial institutions fully support its sustainability